Parental feeding responses to experimental short-term partner removal in a species with male and female brood desertion - Cantarero Alejandro; Plaza Mirea; Moreno Juan; Griggio Matteo (Springer, 2022)
As parental care is costly, it can be expected that there will be a sexual conflict between parents over the individual levels of parental investment because each parent has limited resources to invest in a reproductive event. Theoretical models of parental investment predict that when one parent reduces its parental effort, the other parent should adjust its effort facultatively to compensate for the decrease in the mate’s contribution. Here, we tested for facultative adjustments in care in the rock sparrow, Petronia petronia. In this species, both sexes can desert the brood, creating the potential for strong sexual conflict over parental care to occur. To that end, we examined how rock sparrow parents adjust their level of care in response to an experimental mate removal for a limited time period, mimicking the starting phase of the desertion process. We compared male and female provisioning rates before and after an experimental mate removal. Males behaved according to the prediction of compensatory adjustment, as they allocated more care to the offspring and returned faster to the nest after female removal, whereas females showed no response. Our study shows sexual differences in response to mate removal in a species with biparental care and strong sexual conflict over parental care, and suggests that males may use the female absence to determine their actual parental effort.